Function of an ophthalmic "accident and emergency" department: results of a six month survey. Issue 6514 (18th January 1986) - Jones, N P; Hayward, J M; Khaw, P T; Claoué, C M; Elkington, A R
Abstract : A retrospective analysis was carried out of all patients attending the casualty department of Southampton Eye Hospital during 1 February to 31 July 1983. During the six month period 8092 patients made a total of 13 544 visits. Of these patients, 6178 were attending the hospital for the first time and 1914 had previously been seen in the outpatient clinic; many did not fall into the category of "accident and emergency." Some 37% of patients were managed by the ophthalmic nurse alone. The findings show that the department was providing a service far in excess of its defined function, which suggests that the structure of the acute ophthalmic services may require change. Certainly the value of the ophthalmic nurse was beyond question, her active participation in management allowing the doctor more time with the more complex clinical problems and thus enhancing efficiency.